2004
DOI: 10.1164/rccm.200308-1107oc
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Alveoli in the Human Lung

Abstract: The number of alveoli is a key structural determinant of lung architecture. A design-based stereologic approach was used for the direct and unbiased estimation of alveolar number in the human lung. The principle is based on two-dimensional topology in three-dimensional space and is free of assumptions on the shape, size, or spatial orientation of alveoli. Alveolar number is estimated by counting their openings at the level of the free septal edges, where they form a two-dimensional network. Mathematically, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
443
3
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 609 publications
(483 citation statements)
references
References 30 publications
26
443
3
11
Order By: Relevance
“…Recently, Ochs et al (33) found a mean number of 480 million alveoli in six human lungs with an average diameter of 200 m, which again correlates well with the X rms,1 displacement. X rms,2 compares well with the diameter estimates of TB and RB (384 -411 m) as suggested by Schreider and Raabe (32).…”
Section: Discussionsupporting
confidence: 56%
“…Recently, Ochs et al (33) found a mean number of 480 million alveoli in six human lungs with an average diameter of 200 m, which again correlates well with the X rms,1 displacement. X rms,2 compares well with the diameter estimates of TB and RB (384 -411 m) as suggested by Schreider and Raabe (32).…”
Section: Discussionsupporting
confidence: 56%
“…Because alveoli are not discrete, separate particles, but rather a set of open saccules, it is impossible to count their number in the ordinary way with disectors. This problem was only recently resolved (Hyde et al, 2004;Ochs et al, 2004) by estimating the Euler number of the network of the free septal edges using physical disectors. One of the first applications of this new method was the characterization of postnatal lung development of the rhesus monkey.…”
Section: Discussionmentioning
confidence: 99%
“…Hyde et al introduced a design-based stereological approach to count the number of alveoli, and reported that alveolarization continued at least until young adulthood in rhesus monkeys (Hyde et al, 2004(Hyde et al, , 2007. In parallel to Hyde et al, Ochs et al used the same method for the characterization of adult human lungs (Ochs et al, 2004). In our laboratory, we developed an approach to quantify newly forming alveolar septa.…”
Section: Introductionmentioning
confidence: 99%
“…The light microscopic analysis was performed on an Axioskop light microscope (Zeiss, Oberkochen, Germany) connected with the computer-assisted stereological system CAST 2.0 (Olympus, Ballerup, Denmark). On pairs of orcein sections [distance: 3 m; primary magnification (PM): 5ϫ], the alveolar number was estimated as recently described for different mammalian lungs (Hyde et al, 2004;Ochs et al, 2004aOchs et al, , 2004b. From methylene blue sections (PM: 5ϫ), the volume density of parenchyma in the lung and the volume density of alveoli in the parenchyma were estimated and multiplied by the lung volume, providing the total volume of alveoli.…”
Section: Stereological Analysismentioning
confidence: 99%
“…The present study extends these observations and provides a detailed design-based stereological analysis at the level of light and electron microscopy to characterize the phenotype of lung collectindeficient mice. Recently established methods for the direct and unbiased estimation of the number and size of alveoli (Hyde et al, 2004;Ochs et al, 2004a) and of the number and size of type II cells as well as their surfactant-storing lamellar bodies (Ochs et al, 2004b) were chosen to provide new data on lung parenchymal architecture, on the morphology of alveolar type II cells and their lamellar bodies, as well as of alveolar macrophages in mice double deficient in SP-A and SP-D.…”
mentioning
confidence: 99%